Transport of 6-deoxyglucose in Saccharomyces cerevisiae. - Bisson, L F (1983)
The uptake of 6-deoxyglucose was measured in wild-type Saccharomyces cerevisiae, in a double mutant strain lacking activity for hexokinases A and B (hxkl hxk2), in a triple mutant strain lacking activity for both hexokinases and glucokinase (hxkl hxk2 glk), and in the triple mutant with high levels of activity of single kinases restored by introduction of the cloned genes. In the wild-type strain, uptake of the glucose analog showed two components, with Km values of ca. 20 mM ("high affinity") and 250 mM ("low affinity"), respectively. The double mutant also had high- and low-affinity components, but the triple mutant showed only low-affinity uptake. Reintroduction of the single kinases to the triple mutant restored high-affinity uptake. (Other experiments on 6-deoxyglucose uptake are also presented, including the apparent use of the galactose transport system when induced.) These results show that the recent implication of the kinases in transport of glucose (L.F. Bisson and D.G. Fraenkel, Proc. Natl. Acad. Sci. U.S.A. 80:1730-1734, 1983) applies equally to the nonmetabolized analog 6-deoxyglucose and suggests that the role of the kinases in transport is not merely a consequence of metabolism of the transported compound.